Comparison of instructor-led compression-only cardiopulmonary resuscitation and automated external defibrillator training for secondary school students: A multicenter noninferiority randomized trial - Chi Yeung Yeung; Kit Ying So; Helen Hoi Ting Cheung; Pik Yi Hou; Hiu Fai Ko; Anna Lee (Resuscitation Plus, 2023)
Background: Many barriers exist to the wider and sustainable implementation of basic life support (BLS) training in secondary schools. Whether trained teacher instructors are not worse than healthcare instructors by 20% (noninferiority margin) of simulated BLS skills for secondary school students is unclear. Methods: We conducted a two-armed, parallel, noninferiority, blinded, randomized controlled trial at four secondary schools in Hong Kong after teachers had undergone BLS training. Students were randomized to either the trained teacher or healthcare instructor group for the 2-hour compression-only cardiopulmonary resuscitation and automated external defibrillator (CO-CPRAED) course. The assessors for the students’ BLS skill performance six months after the CO-CPRAED course were blinded. Results: Of the 33 trained teachers, 13 (39.4%) volunteered to be instructors for the CO-CPRAED course. Three hundred and eleven students (median age: 15 years, 67% males) were randomized to either the teacher (n = 161) or healthcare (n = 150) instructor group. The BLS skill performance passing rate (%) at six months was high in both instructor groups (teacher: 88% versus healthcare: 91%; mean difference: −3%, 95% CI: −11% to 5%; P = 0.22). The students’ knowledge levels remained high (>90%) and were similar between instructor groups at six months (P = 0.91). The teachers’ willingness to teach BLS to students was mildly positive. However, the students were extremely positive towards learning and performing BLS. Conclusions: A brief 2-hour CO-CPRAED intervention by trained teachers was noninferior to healthcare instructors and it was associated with students’ very positive attitudes towards CPR, and retention of knowledge and BLS skills.